Attapulgite modified polycarboxylate superplasticizer and preparation method thereof

Through the graft modification method, the modified concave and convex rod soil forms chemical bonding with the polycarboxylic acid molecule, solving the problem of poor stability of the existing polycarboxylic acid water reducer in high temperature and alkaline environments, and improving the water reducer Dispersibility and strength and durability of concrete.

CN119463066AActive Publication Date: 2025-02-18YUETUO TECH (BEIJING) CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411518204.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-18
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

The existing polycarboxylic acid water reducers have poor stability in high temperature and alkaline environments, complex synthesis process and high cost, and the compatibility between the concave and convex rod soil and the polycarboxylic acid water reducers is weak, which affects the stability of the material system.

Method used

By mixing the silane coupling agent with the concave and concave and concave soil after acid-base treatment, reacting and dispersing it ultrasonically to obtain the modified concave and concave soil, then mixing it with polycarboxylic acid monomer and initiator, pre-reaction and graft modification , a concave and convex rod earth-modified polycarboxylic acid water reducing agent was prepared.

Benefits of technology

The interface bonding force between the concave and convex rod soil and polycarboxylic acid molecules is significantly enhanced, the dispersion, stability and performance of the water reducing agent is improved, the compressive strength and durability of concrete are enhanced, and the water consumption of concrete is reduced.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of concrete admixtures, and particularly relates to an attapulgite modified polycarboxylic acid water reducing agent and a preparation method thereof, and the water reducing agent is formed by compounding polycarboxylic acid and modified attapulgite; the modified attapulgite is directly grafted into a polycarboxylic acid molecular structure through an active group; the preparation method of the water reducing agent comprises the following specific steps: S1, uniformly mixing a silane coupling agent with attapulgite subjected to acid and alkali treatment for reaction, and after the reaction is finished, performing ultrasonic dispersion to obtain modified attapulgite; s2, uniformly mixing a polycarboxylic acid monomer and an initiator for pre-reaction, adding the modified attapulgite for reaction after the pre-reaction is finished, and washing and drying to obtain the attapulgite modified polycarboxylic acid water reducer. Through a grafting modification technology, the interaction between the attapulgite and polycarboxylic acid molecules is more stable and effective, and the working performance of the water reducing agent is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of concrete admixtures, and particularly relates to an attapulgite-modified polycarboxylic acid water-reducing agent and a preparation method thereof. Background Art

[0002] Polycarboxylate superplasticizers are widely used in the concrete field due to their excellent water-reducing effect and good adaptability. However, existing polycarboxylate superplasticizers have poor stability in high temperature and alkaline environments, and their synthesis process is complex and costly.

[0003] Attapulgite is a clay mineral with unique structure and properties, which is widely used in various industrial fields. Attapulgite can be used in combination with polycarboxylate water reducer to improve the dispersibility, adhesion and water retention of water reducer. The combination of attapulgite and polycarboxylate water reducer has some specific advantages, but also some disadvantages.

[0004] The specific advantage is that it can improve dispersibility: Attapulgite has a nano-scale fibrous structure and a high specific surface area. When used in combination with polycarboxylate water reducer, it can provide more adsorption sites, which helps the water reducer to disperse better in the concrete system. This dispersion effect is conducive to improving the uniform distribution of cement particles and improving the working performance of concrete.

[0005] Enhanced cohesion: Attapulgite has strong cohesive properties and can form a certain cohesive network in the concrete paste. By compounding with polycarboxylate water reducer, it can improve the cohesiveness of concrete, reduce the bleeding of concrete, and improve the anti-segregation performance of concrete, especially in self-compacting concrete with high slump.

[0006] Improve water retention: The adsorption capacity of attapulgite enables it to retain water in concrete, reduce water loss, and prevent shrinkage cracks in the concrete during the hardening process. This is especially important for concrete construction in high temperature and dry environments.

[0007] Green and environmentally friendly: Attapulgite is a natural mineral material with good chemical stability and low cost. Its environmentally friendly and non-toxic characteristics are in line with the current development trend of green building materials, reducing the proportion of organic chemicals in the water reducing agent system and improving environmental friendliness.

[0008] However, the existing modified polycarboxylate water-reducing agent prepared by mixing also has the following shortcomings:

[0009] Excessive dispersibility affects the water-reducing effect: While the high adsorption of attapulgite improves dispersibility, it may also adsorb the active components of polycarboxylic acid water-reducing agent, causing the effective ingredients of the water-reducing agent to be weakened, affecting its adsorption and dispersion ability on cement particles, and thus causing the water-reducing effect to be less than expected.

[0010] Negative impact on viscosity: Although the cohesiveness of attapulgite can improve the cohesiveness of concrete, in some cases, this cohesiveness may lead to an increase in the viscosity of the slurry, affecting the fluidity of the concrete and increasing the difficulty of pumping. This may have an adverse effect on concrete that requires high fluidity or self-leveling.

[0011] Compatibility with polycarboxylate water reducer: Attapulgite is an inorganic material, and its compatibility with organic polymers (such as polycarboxylate water reducer) is weak, which may affect the synergistic effect between the two. It is necessary to improve the compatibility of attapulgite through surface modification or functionalization treatment, otherwise it may lead to instability of the material system.

[0012] Impact on early strength: The water retention of attapulgite may slow down the hydration reaction of concrete, especially in low temperature environments, which may slow down the growth of early strength of concrete and affect the progress of construction. Therefore, its use may need to be weighed in some projects that require rapid strength growth.

[0013] Therefore, it is of great significance to overcome this problem through reasonable design and modification and develop a new attapulgite-modified polycarboxylic acid water-reducing agent. Summary of the invention

[0014] The technical problem to be solved by the present invention is to provide a attapulgite-modified polycarboxylic acid water reducer in view of the deficiencies in the prior art. The water reducer is composited with polycarboxylic acid and modified attapulgite; the modified attapulgite is directly grafted into the polycarboxylic acid molecular structure through active groups.

[0015] In order to solve the above technical problems, the present invention discloses a method for preparing a attapulgite-modified polycarboxylate water-reducing agent, which comprises the following specific steps:

[0016] S1. The silane coupling agent and the acid-base treated attapulgite are mixed evenly and reacted, and after the reaction, ultrasonic dispersion is performed to obtain modified attapulgite;

[0017] S2. The polycarboxylic acid monomer and the initiator are mixed uniformly for pre-reaction. After the pre-reaction, modified attapulgite is added for further reaction. After washing and drying, a powdered attapulgite-modified polycarboxylic acid water reducer is obtained.

[0018] Preferably, sodium hydroxide solution is added to the powdered attapulgite-modified polycarboxylate water-reducing agent prepared in S2 to adjust the pH to 4-6, and then diluted to obtain the liquid attapulgite-modified polycarboxylate water-reducing agent.

[0019] Among them, in S1, the mass ratio of the silane coupling agent to the attapulgite after acid-base treatment is 1: (30-50); the silane coupling agent exists in the form of an alcohol solution, wherein the mass ratio of the silane coupling agent to the alcohol is 1: 200; the silane coupling agent is KH-570.

[0020] Preferably, the acid-base treatment process of the attapulgite is to first treat it with 1M HCl for 30 minutes and then treat it with 1M NaOH for 40 minutes;

[0021] More preferably, the particle size of the attapulgite is 20-200 mesh.

[0022] Wherein, in S1, the reaction conditions of the silane coupling agent and the acid-base treated attapulgite are a temperature of 40 to 60° C. and a reaction time of 4 to 6 hours.

[0023] In S1, the ultrasonic dispersion conditions are dispersion for 15 to 30 minutes and the ultrasonic intensity is 2 to 5 W / cm 2 .

[0024] Among them, in S2, the polycarboxylic acid monomer includes: by mass percentage, 30-50% acrylic acid (AA), 30-40% methacrylic acid (MAA), 10-40% hydroxyethyl acrylate (HEA) and / or hydroxypropyl acrylate (HPA); the amount of the initiator used is 0.4-1.0% of the polycarboxylic acid monomer by mass percentage.

[0025] Preferably, the initiator is potassium persulfate (KPS).

[0026] Wherein, in S2, the pre-reaction conditions are a temperature of 60 to 80° C. and a reaction time of 2 to 3 hours.

[0027] Wherein, in S2, the usage amount of the modified attapulgite is 5-10% of the polycarboxylic acid monomer by mass percentage.

[0028] Wherein, in S2, the reaction time after adding the modified attapulgite is 1 to 2 hours.

[0029] Specifically, in some embodiments of the present invention, by adding the above-mentioned attapulgite modified polycarboxylic acid water-reducing agent as one of the concrete admixtures into concrete, and testing the water reduction rate, slump and compressive strength of the concrete, the feasibility of using the above-mentioned attapulgite modified polycarboxylic acid water-reducing agent in concrete admixtures is verified.

[0030] Beneficial effects: The difference between the grafting modification of attapulgite and direct mixing is that the grafting modification can achieve chemical bonding between attapulgite and polycarboxylic acid molecules, thereby significantly enhancing their interfacial bonding and overall performance. This modification mainly achieves the following effects by introducing active groups on the surface of attapulgite or grafting polymer chains to the surface of attapulgite through covalent bonds:

[0031] (1) Chemical bonding enhancement

[0032] During the grafting modification process, the surface active sites of attapulgite (such as hydroxyl groups, silicon-oxygen bonds, etc.) and the functional groups of polycarboxylic acid (such as carboxyl groups, hydroxyl groups, epoxy groups, etc.) form stable covalent bonds through chemical reactions. This chemical bonding enables the modified attapulgite to more firmly bind to the polycarboxylic acid molecules, avoiding mutual separation in the cement system and improving the overall performance of the water reducer;

[0033] (2) Improved dispersion and stability

[0034] The dispersibility of grafted attapulgite in cement paste is significantly improved. Compared with direct physical mixing, grafting modification reduces the agglomeration effect of polymers by enhancing the interfacial bonding force, so that the modified attapulgite can be more evenly and stably distributed in the system and maintain a longer active action time.

[0035] (3) Surface performance control

[0036] Graft modification can precisely regulate the hydrophilicity and lipophilicity of the surface of attapulgite. By introducing different graft chains, its hydrophilicity or hydrophobicity can be enhanced directionally, thereby optimizing the dispersion, adsorption and rheological properties of polycarboxylate water reducer. This regulation capability cannot be achieved by direct mixing.

[0037] (4) Intermolecular synergy

[0038] There is not only electrostatic repulsion and steric hindrance effect between the grafted modified attapulgite and the polycarboxylic acid molecules, but also synergistic effect of chemical bonds. This synergistic effect can more effectively enhance the adsorption capacity of the water reducer in the cement paste, reduce the water consumption in the concrete, and improve the strength and durability of the concrete.

[0039] Compared with direct mixing, the grafting modification technology makes the interaction between attapulgite and polycarboxylic acid molecules more stable and effective, significantly improving the working performance of the water reducer and increasing the water reduction rate in actual use: after grafting modification, the attapulgite and polycarboxylic acid molecules are more tightly combined, significantly improving the dispersion performance of the water reducer, reducing the water consumption of concrete, and improving the fluidity of cement paste;

[0040] Enhance concrete strength: The modified attapulgite improves the microstructure of cement paste, increases the compressive strength and flexural strength of concrete, and enhances its durability;

[0041] Prolonging the action time: Graft modification makes the combination of attapulgite and water reducer more stable, prolonging the effective time of water reducer in concrete and improving the operability of construction;

[0042] Improve adsorption efficiency: The adsorption capacity of the modified attapulgite surface and cement particles is enhanced, which reduces the loss of polycarboxylic acid water reducer in the slurry and improves the use efficiency of the water reducer;

[0043] Optimize interface performance: Graft modification significantly improves the interface performance between attapulgite and polycarboxylic acid, promotes the uniform distribution of cement particles, and reduces slump loss. DETAILED DESCRIPTION

[0044] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials are commercially available unless otherwise specified; the performance test methods for the water reducer products in the following examples are conventional methods for evaluating the performance of water reducers in the art.

[0045] Embodiment 1:

[0046] (1) Modification of attapulgite

[0047] 100 g of attapulgite with a moderate particle size (20-200 mesh) was selected for surface acid-base treatment, wherein 1 M HCl was used as the acid for 30 min, and 1 M NaOH was used as the alkali for 40 min to obtain the attapulgite after acid-base treatment;

[0048] The acid-base treated attapulgite was further modified using 2 g of silane coupling agent KH-570, and the coupling agent and solvent were mixed at a mass ratio of 1:200 to prepare a coupling agent solution, wherein the solvent was methanol or ethanol; the coupling agent solution was evenly mixed with the acid-base treated attapulgite, and the mixture was reacted at a reaction temperature of 40 °C for 4 h to introduce active groups such as hydroxyl or carboxyl groups on the surface of the attapulgite to enhance its binding force with the polycarboxylic acid molecules; the product after the reaction was dispersed using ultrasound for 15 min, and the ultrasound intensity was 2 W / cm 2 After dispersion, silane coupling agent modified attapulgite is obtained with a particle size of 200-400nm.

[0049] (2) Preparation of polycarboxylate water reducer

[0050] In a reactor, a polycarboxylic acid matrix is ​​synthesized according to a conventional process, and the monomer ratio and reaction conditions are controlled during the synthesis process. The monomers are added to the reactor according to the following composition, specifically: 30 g of acrylic acid (AA), 40 g of methacrylic acid (MAA), and the rest are 30 g of hydroxyethyl acrylate (HEA) or hydroxypropyl acrylate (HPA), and an initiator: potassium persulfate (KPS), 0.4 g; the reaction temperature is 60°C, and the pre-reaction time is 2 hours; after the pre-reaction, 5 g of attapulgite modified by a silane coupling agent is added, and the reaction is continued for another 1 hour. The obtained modified polycarboxylic acid water reducer is washed and dried to obtain a powdered attapulgite modified polycarboxylic acid water reducer. The surface energy of the powdered attapulgite modified polycarboxylic acid water reducer is detected by a contact angle method or a surface tension method. After detection, the surface energy is 80 mN / m. Subsequently, the above powder is added with a sodium hydroxide solution to adjust the pH to 4, and diluted to obtain a liquid attapulgite modified polycarboxylic acid water reducer.

[0051] The water reducing agent product has excellent performance, and the water reducing rate can reach 16%. The dosage is 0.5% of the cement dosage. Compared with the use of ordinary water reducing agent (naphthalene series water reducing agent) under the same water-cement ratio, the slump can be increased by more than 10cm and the compressive strength can be increased by more than 15%.

[0052] Embodiment 2:

[0053] (1) Modification of attapulgite

[0054] 100 g of attapulgite with a moderate particle size (20-200 mesh) was selected for surface acid-base treatment, wherein 1M HCl was used as the acid for 30 min and 1M NaOH was used as the alkali for 38 min to obtain the attapulgite after acid-base treatment;

[0055] The acid-base treated attapulgite was further modified using 2.2 g of silane coupling agent KH-570, and the coupling agent and solvent were mixed at a mass ratio of 1:200 to prepare a coupling agent solution, wherein the solvent was methanol or ethanol; the coupling agent solution was evenly mixed with the acid-base treated attapulgite, and the mixture was reacted at a reaction temperature of 45 °C for 6 h to introduce active groups such as hydroxyl or carboxyl groups onto the surface of the attapulgite to enhance its binding force with the polycarboxylic acid molecules; the product after the reaction was dispersed using ultrasound for 20 min, and the ultrasound intensity was 3 W / cm 2 After the dispersion is completed, silane coupling agent modified attapulgite is obtained, and the particle size is 200-400nm.

[0056] (2) Preparation of polycarboxylate water reducer

[0057] In a reactor, a polycarboxylic acid matrix is ​​synthesized according to a conventional process, and the monomer ratio and reaction conditions are controlled during the synthesis process. The monomers are added to the reactor according to the following composition, specifically: 35g of acrylic acid (AA), 38g of methacrylic acid (MAA), 27g of hydroxyethyl acrylate (HEA) or hydroxypropyl acrylate (HPA), and 0.5g of initiator: potassium persulfate (KPS); reaction temperature 65°C, pre-reaction time 2.5h; after the pre-reaction, 6g of attapulgite modified by silane coupling agent is added, and the reaction is continued for another 1.5h. The obtained modified polycarboxylic acid water reducer is washed and dried to obtain a powdered attapulgite modified polycarboxylic acid water reducer. The surface energy of the powdered attapulgite modified polycarboxylic acid water reducer is detected by a contact angle method or a surface tension method. After detection, the surface energy is 90mN / m. Subsequently, the above powder is added with a sodium hydroxide solution to adjust the pH to 6.5, and diluted to obtain a liquid attapulgite modified polycarboxylic acid water reducer.

[0058] The water reducer prepared in this embodiment was tested by the same water reducer product performance test method. The test results showed that the water reducing rate of the water reducer prepared in this embodiment could reach 16%. The dosage was 0.5% of the cement dosage. Compared with the use of ordinary water reducer (naphthalene-based water reducer) under the same water-cement ratio, the slump could be increased by more than 10 cm and the compressive strength by more than 15%.

[0059] Embodiment 3:

[0060] (1) Modification of attapulgite

[0061] 100 g of attapulgite with a moderate particle size (20-200 mesh) was selected for surface acid-base treatment, wherein 1 M HCl was used as the acid for 40 min, and 1 M NaOH was used as the alkali for 20 min to obtain the acid-base treated attapulgite;

[0062] The acid-base treated attapulgite was further modified using 2.4 g of silane coupling agent KH-570, and the coupling agent and solvent were mixed at a mass ratio of 1:200 to prepare a coupling agent solution, wherein the solvent was methanol or ethanol; the coupling agent solution was evenly mixed with the acid-base treated attapulgite, and the reaction was carried out at a reaction temperature of 50 °C for 5 h to introduce active groups such as hydroxyl or carboxyl groups on the surface of the attapulgite to enhance its binding force with the polycarboxylic acid molecules; the product after the reaction was dispersed using ultrasound for 30 min, and the ultrasound intensity was 4 W / cm 2 After dispersion, silane coupling agent modified attapulgite is obtained with a particle size of 200-400nm.

[0063] (2) Preparation of polycarboxylate water reducer

[0064] In a reactor, a polycarboxylic acid matrix is ​​synthesized according to a conventional process, and the monomer ratio and reaction conditions are controlled during the synthesis process. The monomers are added to the reactor according to the following composition, specifically: 40g of acrylic acid (AA), 36g of methacrylic acid (MAA), 24g of hydroxyethyl acrylate (HEA) or hydroxypropyl acrylate (HPA), and 0.7g of initiator: potassium persulfate (KPS); reaction temperature 70°C, pre-reaction time 3h; after the pre-reaction, 7g of attapulgite modified by silane coupling agent is added, and the reaction is continued for another 1h. The obtained modified polycarboxylic acid water reducer is washed and dried to obtain a powdered attapulgite modified polycarboxylic acid water reducer. The surface energy of the powdered attapulgite modified polycarboxylic acid water reducer is detected by a contact angle method or a surface tension method. After detection, the surface energy is 80mN / m. Subsequently, the above powder is added with a sodium hydroxide solution to adjust the pH to 7, and diluted to obtain a liquid attapulgite modified polycarboxylic acid water reducer.

[0065] The water reducer prepared in this embodiment was tested by the same water reducer product performance test method. The test results showed that the water reducing rate of the water reducer prepared in this embodiment could reach 10%. The dosage was 0.7% of the cement dosage. Compared with the use of ordinary water reducer (naphthalene-based water reducer) under the same water-cement ratio, the slump could be increased by more than 7 cm and the compressive strength by more than 13%.

[0066] Embodiment 4:

[0067] (1) Modification of attapulgite

[0068] 100 g of attapulgite with a moderate particle size (20-200 mesh) was selected for surface acid-base treatment, wherein 1 M HCl was used as the acid for 45 min, and 1 M NaOH was used as the alkali for 25 min to obtain the acid-base treated attapulgite;

[0069] The acid-base treated attapulgite was further modified using 2.6 g of silane coupling agent KH-570, and the coupling agent and solvent were mixed at a mass ratio of 1:200 to prepare a coupling agent solution, wherein the solvent was methanol or ethanol; the coupling agent solution was evenly mixed with the acid-base treated attapulgite, and the mixture was reacted at a reaction temperature of 60 °C for 5 h to introduce active groups such as hydroxyl or carboxyl groups on the surface of the attapulgite to enhance its binding force with the polycarboxylic acid molecules; the product after the reaction was dispersed using ultrasound for 15 min, and the ultrasound intensity was 5 W / cm 2 After dispersion, silane coupling agent modified attapulgite is obtained with a particle size of 200-400nm.

[0070] (2) Preparation of polycarboxylate water reducer

[0071] In a reactor, a polycarboxylic acid matrix is ​​synthesized according to a conventional process, and the monomer ratio and reaction conditions are controlled during the synthesis process. The monomers are added to the reactor according to the following composition, specifically: 45g of acrylic acid (AA), 34g of methacrylic acid (MAA), 21g of hydroxyethyl acrylate (HEA) or hydroxypropyl acrylate (HPA), and 0.8g of initiator: potassium persulfate (KPS); reaction temperature 75°C, pre-reaction time 2.5h; after the pre-reaction, 8g of attapulgite modified by a silane coupling agent is added, and the reaction is continued for another 1.5h. The obtained modified polycarboxylic acid water reducer is washed and dried to obtain a powdered attapulgite modified polycarboxylic acid water reducer. The surface energy of the powdered attapulgite modified polycarboxylic acid water reducer is detected by a contact angle method or a surface tension method. After detection, the surface energy is 100mN / m. Subsequently, the above powder is added with a sodium hydroxide solution to adjust the pH to 4, and diluted to obtain a liquid attapulgite modified polycarboxylic acid water reducer.

[0072] The water reducer prepared in this embodiment was tested for performance using the same water reducer product performance test method. The test results showed that the water reducing rate of the water reducer prepared in this embodiment could reach 20%. The dosage was 0.6% of the cement dosage. Compared with the use of ordinary water reducer (naphthalene-based water reducer) under the same water-cement ratio, the slump could be increased by more than 6 cm and the compressive strength by more than 10%.

[0073] Embodiment 5:

[0074] (1) Modification of attapulgite

[0075] 100 g of attapulgite with a moderate particle size (20-200 mesh) was selected for surface acid-base treatment, wherein 1 M HCl was used as the acid for 50 min, and 1 M NaOH was used as the alkali for 34 min to obtain the attapulgite after acid-base treatment;

[0076] The acid-base treated attapulgite was further modified using 2.8 g of silane coupling agent KH-570, and the coupling agent and solvent were mixed at a mass ratio of 1:200 to prepare a coupling agent solution, wherein the solvent was methanol or ethanol; the coupling agent solution was evenly mixed with the acid-base treated attapulgite, and the mixture was reacted at a reaction temperature of 55 °C for 6 h to introduce active groups such as hydroxyl or carboxyl groups onto the surface of the attapulgite to enhance its binding force with the polycarboxylic acid molecules; the product after the reaction was dispersed using ultrasound for 30 min, and the ultrasound intensity was 4 W / cm 2 After dispersion, silane coupling agent modified attapulgite is obtained with a particle size of 200-400nm.

[0077] (2) Preparation of polycarboxylate water reducer

[0078] In a reactor, a polycarboxylic acid matrix is ​​synthesized according to a conventional process, and the monomer ratio and reaction conditions are controlled during the synthesis process. The monomers are added to the reactor according to the following composition, specifically: 50 g of acrylic acid (AA), 32 g of methacrylic acid (MAA), 18 g of hydroxyethyl acrylate (HEA) or hydroxypropyl acrylate (HPA), and 1 g of initiator: potassium persulfate (KPS); reaction temperature 80°C, pre-reaction time 3 h; after the pre-reaction, 9 g of attapulgite modified by a silane coupling agent is added, and the reaction is continued for another 1.2 h. The obtained modified polycarboxylic acid water reducer is washed and dried to obtain a powdered attapulgite modified polycarboxylic acid water reducer. The surface energy of the powdered attapulgite modified polycarboxylic acid water reducer is detected by a contact angle method or a surface tension method. After detection, the surface energy is 75 mN / m. Subsequently, the above powder is added with a sodium hydroxide solution to adjust the pH to 7, and diluted to obtain a liquid attapulgite modified polycarboxylic acid water reducer.

[0079] The water reducer prepared in this embodiment was tested by the same water reducer product performance test method. The test results showed that the water reducing rate of the water reducer prepared in this embodiment could reach 12%. The dosage was 1% of the cement dosage. Compared with the use of ordinary water reducer (naphthalene-based water reducer) under the same water-cement ratio, the slump could be increased by more than 5 cm and the compressive strength by more than 14%.

[0080] Embodiment 6:

[0081] (1) Modification of attapulgite

[0082] 100 g of attapulgite with a moderate particle size (20-200 mesh) was selected for surface acid-base treatment, wherein 1 M HCl was used as the acid for 30 min, and 1 M NaOH was used as the alkali for 36 min to obtain the attapulgite after acid-base treatment;

[0083] The acid-base treated attapulgite was further modified using 3 g of silane coupling agent KH-570, and the coupling agent and solvent were mixed at a mass ratio of 1:200 to prepare a coupling agent solution, wherein the solvent was methanol or ethanol; the coupling agent solution was evenly mixed with the acid-base treated attapulgite, and the reaction was carried out at a reaction temperature of 40 °C for 4 h to introduce active groups such as hydroxyl or carboxyl groups on the surface of the attapulgite to enhance its binding force with the polycarboxylic acid molecules; the product after the reaction was dispersed using ultrasound for 20 min, and the ultrasound intensity was 3 W / cm 2 After dispersion, silane coupling agent modified attapulgite is obtained with a particle size of 200-400nm.

[0084] (2) Preparation of polycarboxylate water reducer

[0085] In a reactor, a polycarboxylic acid matrix is ​​synthesized according to a conventional process, and the monomer ratio and reaction conditions are controlled during the synthesis process. The monomers are added to the reactor according to the following composition, specifically: 45g of acrylic acid (AA), 34g of methacrylic acid (MAA), 21g of hydroxyethyl acrylate (HEA) or hydroxypropyl acrylate (HPA), and 0.9g of initiator: potassium persulfate (KPS); reaction temperature 75°C, pre-reaction time 2.5h; after the pre-reaction, 10g of attapulgite modified by a silane coupling agent is added, and the reaction is continued for another 1h. The obtained modified polycarboxylic acid water reducer is washed and dried to obtain a powdered attapulgite modified polycarboxylic acid water reducer. The surface energy of the powdered attapulgite modified polycarboxylic acid water reducer is detected by a contact angle method or a surface tension method. After detection, the surface energy is 95mN / m. Subsequently, the above powder is added with a sodium hydroxide solution to adjust the pH to 6, and diluted to obtain a liquid attapulgite modified polycarboxylic acid water reducer.

[0086] The water reducer prepared in this embodiment was tested for performance using the same water reducer product performance test method. The test results showed that the water reducing rate of the water reducer prepared in this embodiment could reach 18%. The dosage was 0.9% of the cement dosage. Compared with the use of ordinary water reducer (naphthalene-based water reducer) under the same water-cement ratio, the slump could be increased by more than 8 cm and the compressive strength by more than 13%.

[0087] The present invention provides a attapulgite-modified polycarboxylate water-reducing agent and a preparation method thereof. There are many methods and approaches to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention. All components not specified in this embodiment can be implemented by existing technologies.

Claims

1. A attapulgite-modified polycarboxylate water-reducing agent, characterized in that: The water reducing agent is composited by polycarboxylic acid and modified attapulgite; the modified attapulgite is directly grafted into the molecular structure of polycarboxylic acid through active groups.

2. A method for preparing an attapulgite-modified polycarboxylate water-reducing agent, characterized in that: The specific steps are: S1. The silane coupling agent and the acid-base treated attapulgite are mixed evenly and reacted, and after the reaction, ultrasonic dispersion is performed to obtain modified attapulgite; S2. The polycarboxylic acid monomer and the initiator are mixed uniformly for pre-reaction. After the pre-reaction, modified attapulgite is added for further reaction. After washing and drying, attapulgite-modified polycarboxylic acid water reducer is obtained.

3. The preparation method according to claim 2, characterized in that: In S1, the mass ratio of the silane coupling agent to the acid-base treated attapulgite is 1:(30-50); the silane coupling agent exists in the form of an alcohol solution, wherein the mass ratio of the silane coupling agent to the alcohol is 1:200; the silane coupling agent is KH-570.

4. The preparation method according to claim 3, characterized in that: In S1, the reaction conditions of the silane coupling agent and the acid-base treated attapulgite are a temperature of 40 to 60° C. and a reaction time of 4 to 6 hours.

5. The preparation method according to claim 2, characterized in that: In S1, the ultrasonic dispersion conditions are dispersion for 15 to 30 minutes and the ultrasonic intensity is 2 to 5 W / cm 2 .

6. The preparation method according to claim 2, characterized in that: In S2, the polycarboxylic acid monomer includes: by mass percentage, 30-50% acrylic acid, 30-40% methacrylic acid, 10-40% hydroxyethyl acrylate and / or hydroxypropyl acrylate; the amount of the initiator used is 0.4-1.0% of the polycarboxylic acid monomer by mass percentage.

7. The preparation method according to claim 2, characterized in that: In S2, the pre-reaction conditions are a temperature of 60 to 80° C. and a reaction time of 2 to 3 hours.

8. The preparation method according to claim 2, characterized in that: In S2, the modified attapulgite is used in an amount of 5 to 10% by mass of the polycarboxylic acid monomer.

9. The preparation method according to claim 2, characterized in that: In the S2, the reaction time after adding the modified attapulgite is 1 to 2 hours.

10. A concrete admixture, characterized in that: The concrete admixture comprises the attapulgite-modified polycarboxylate water-reducing agent according to claim 1.

Citation Information

Patent Citations

  • High-slump-retaining polycarboxylic acid composite water reducer and preparation method thereof

    CN106082759A

  • Silane coupling agent modification method of attapulgite

    CN106975454A

  • Preparation method of nano attapulgite bonding composite material

    CN108774035A

  • Foam concrete and preparation method and application thereof

    CN113264725A

  • Composite polycarboxylic acid water reducer

    CN114516733A